A Novel Model of Mixed Vascular Dementia Incorporating Hypertension in a Rat Model of Alzheimer’s Disease - Denver, Paul; D’Adamo, Heather; Hu, Shuxin; Zuo, Xiaohong; Zhu, Cansheng; Okuma, Chihiro; Kim, Peter; Castro, Daniel; Jones, Mychica R.; Leal, Carmen; Mekkittikul, Marisa; Ghadishah, Elham; et al. (Frontiers in Physiology, 2019)
Alzheimer’s disease (AD) and mixed dementia (MxD) comprise the majority of dementia cases in the growing global aging population. MxD describes the coexistence of AD pathology with vascular pathology, including cerebral small vessel disease (SVD). Cardiovascular disease increases risk for AD and MxD, but mechanistic synergisms between the coexisting pathologies affecting dementia risk, progression and the ultimate clinical manifestations remain elusive. To explore the additive or synergistic interactions between AD and chronic hypertension, we developed a rat model of MxD, produced by breeding APPswe/PS1ΔE9 transgenes into the stroke-prone spontaneously hypertensive rat (SHRSP) background, resulting in the SHRSP/FAD model and three control groups (FAD, SHRSP and non-hypertensive WKY rats, n=8-11, both sexes, 16-18 months of age). After behavioral testing, rats were euthanized, and tissue assessed for vascular, neuroinflammatory and AD pathology. Hypertension was preserved in the SHRSP/FAD cross. Results showed that SHRSP increased FAD-dependent neuroinflammation (microglia and astrocytes) and tau pathology, but plaque pathology changes were subtle, including fewer plaques with compact cores and slightly reduced plaque burden. Evidence for vascular pathology included a change in the distribution of astrocytic end-foot protein aquaporin-4, normally distributed in microvessels, but in SHRSP/FAD rats largely dissociated from vessels, appearing disorganized or redistributed into neuropil. Other evidence of SVD-like pathology included increased collagen IV staining in cerebral vessels and PECAM1 levels. We identified a plasma biomarker in SHRSP/FAD rats that was the only group to show increased Aqp-4 in plasma exosomes. Evidence of neuron damage in SHRSP/FAD rats included increased caspase-cleaved actin, loss of myelin and reduced calbindin staining in neurons. Further, there were mitochondrial deficits specific to SHRSP/FAD, notably the loss of complex II, accompanying FAD-dependent loss of mitochondrial complex I. Cognitive deficits exhibited by FAD rats were not exacerbated by the introduction of the SHRSP phenotype, nor was the hyperactivity phenotype associated with SHRSP altered by the FAD transgene. This novel rat model of mixed dementia, encompassing an amyloidogenic transgene with a hypertensive phenotype, exhibits several features associated with human vascular or “mixed” dementia and may be a useful tool in delineating the pathophysiology of MxD and development of therapeutics.